2012
DOI: 10.1007/s00464-012-2413-2
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison of open versus laparoscopic management of splenic artery aneurysms: a 10-year study

Abstract: Background The literature does not support the choice between open and laparoscopic management of splenic artery aneurysms (SAA). Methods We designed a prospective, randomized comparison between open and laparoscopic surgery for SAA. Primary end points were types of surgical procedures performed and clinical outcomes. Analysis was developed on an intention-to-treat basis. Results Fourteen patients were allocated to laparotomy (group A) and 15 to laparoscopy (group B). Groups displayed similar patient-and aneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 25 publications
0
33
1
1
Order By: Relevance
“…It was statistically different from laparoscopic approach 125 ± 34 min. 33 In our department, the duration of surgery (mean 122 ± 55 min) was not significantly different from Tiberio’s results. Mean blood loss in our department was 36 ± 36 ml, which was significantly lower than that reported in literature.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…It was statistically different from laparoscopic approach 125 ± 34 min. 33 In our department, the duration of surgery (mean 122 ± 55 min) was not significantly different from Tiberio’s results. Mean blood loss in our department was 36 ± 36 ml, which was significantly lower than that reported in literature.…”
Section: Discussioncontrasting
confidence: 53%
“…First randomised controlled trial comparing open with laparoscopic approach was performed by Tiberio et al. 33 Mean time of open surgery was 190 ± 48 min. It was statistically different from laparoscopic approach 125 ± 34 min.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study conducted by Tiberio et al 52 involving 29 SAA patients who were randomized to either laparoscopy or laparotomy, the laparoscopy group had lower morbidity rates, shorter hospital stays and more rapid recoveries. The 13.3% conversion rate from laparoscopic to open surgery was due to concomitant involvement of the pancreatic tail, and iatrogenic vessel tear during dissection 52.…”
Section: Splenic Artery Aneurysm/pseudoaneurysmmentioning
confidence: 98%
“…The 13.3% conversion rate from laparoscopic to open surgery was due to concomitant involvement of the pancreatic tail, and iatrogenic vessel tear during dissection 52. Although, it was reported that laparoscopic repair cannot be done in cases of an SAA rupture, Kim et al 53 was able to successfully repair a ruptured SAA laparoscopically.…”
Section: Splenic Artery Aneurysm/pseudoaneurysmmentioning
confidence: 99%
“…Letztere Autoren führten jedoch eine laparoskopische Splenektomie zur Behandlung des Aneurysmas durch, wie dies auch andere Kasuistiken berichten [12]. Prospektiv randomisiert haben Tiberio et al 14 [13].…”
unclassified